HUBUNGAN TINGKAT PENGETAHUAN TENTANG KANKER PAYUDARA TERHADAP PERILAKU SADARI PADA MAHASISWA FK UMSU ANGKATAN 2019 - Heppy Jelita Batubara (Oceana Biomedicina Journal, 2022)
Referring to the problem of breast cancer, it is necessary to do early detection of breast cancer. Efforts to control breast cancer have been carried out by the Government of Indonesia specifically through an early detection program for cancer in Indonesian women for breast cancer along with an early detection program for cervical cancer. Early detection of breast cancer is an effort to detect and identify breast cancer early or not, so it is hoped that it can be treated with techniques that have little physical impact and have a greater chance of recovery. Cancer is one of the non-communicable diseases that is a public health problem in Indonesia and in the world. The death rate in the world is caused by cancer and is the second killer after cardiovascular disease, namely 12%. Breast cancer is a malignancy in breast tissue that can originate from the ductal epithelium or its lobules. Breast cancer is one of the most common types of cancer in Indonesia. Breast cancer ranks second after cervical cancer which attacks women worldwide. According to GLOBOCAN 2012 the highest incidence of breast cancer in ASEAN is owned by Indonesia at 48,998 and 40.3 per 100,000 women (AISR Age Standardize Incidence Rate), followed by the Philippines at 18,327 (47), Thailand at 13,653 (293) and Malaysia at 5,410 (38.7) The number of cases of breast cancer patients in North Sumatra was 2,682 per 100,000 with a diagnosis prevalence of 0.4%. The data obtained from the study had 98 samples of research respondents who met the inclusion criteria, the results of the study were obtained regarding "The relationship between the level of knowledge about breast cancer and BSE behavior in FK UMSU students Batch 2020 is sufficient. This is indicated by the results of the presentation of a high level of knowledge 48, 45%, moderate as much as 41.24% and low as much as 10.31% The level of knowledge of each student is different.